The use of the Design Science Research method in Information Science: a systematic review of the literature - de Jesus, Ananda Fernanda [UNESP]; Tadini, Antonio Victor Wolf [UNESP]; Pereira, Clayton Martins [UNESP]; Marinho, Ronnie Shida [UNESP]; de Castro, William Pires [UNESP]; Segundo, José Eduardo Santarem [UNESP] (My University, 2023)
Introduction: Design Science Research (DSR) is a method for generating scientific knowledge, through the elaboration of artifacts, with the potential to contribute to the development of research carried out in the field of Information Science. The present study starts from the question: how has the DSR method been applied in Information Science research? The objective is to identify in which lines of research in Information Science has DSR been applied and in what way. Method: A Systematic Literature Review was carried out, analyzing in the accepted articles: a) research topic; b) in which lines and themes of the Information Science area the article fits; and c) degree of adherence of the research to the method. Results: In relation to the research topic, applied research stood out, with the aim of generating artifacts. As for the lines of research, research focused on Information and Knowledge Management and those focused on the development of Information and Communication Technologies stood out. Regarding the level of adhesion, it was observed that the biggest lag is in the process of adequate evaluation of the generated artifacts. Conclusion: DSR can contribute to Information Science, resulting in the development of artifacts with greater scientific rigor and, at the same time, in solving practical problems. The method is still little explored in the area, being necessary to go deeper in its conduction, evaluation of the steps, flows, instruments and complementary methodologies used in the conduction of the DSR, aiming at the creation of a model that supports the execution of future researches.
O uso do método Design Science Research na Ciência da Informação: uma revisão sistemática da literatura
Keywords: DSR; Information Science; Scientific method; Scientific methodology